Aplikasi Pemesanan Online Kaus Kaki Pada UD. Persada Ungaran (Information Technology and Telematics, 2013)
The need for information is not limited to any organization, individupun need. The quality of information is determined by the timeliness and relevance. To meet the need for quality information, required data processing equipment has high speed and accurate results, such as computers. Technological developments in relation to the progress and various easiness offered to make users more pampered in their utilization in a variety of disciplines. The objectives to be achieved is to implement the design into a web-based online store so that it can attract consumers into buying goods sold by UD. Persada Ungaran. The results in this study is with the online booking applications socks at UD. Persada Ungaran can enable customers to conduct sales transactions socks without limitation of time and space and allows consumers to obtain product information socks at UD. Persada Ungaran quickly and easily. Keyword: Pemesanan Online, UD. Persada Ungaran, Kaus Kaki .